Basic Principles of Rational Antibacterial Therapy in the Treatment of Urinary Tract Infections in Children - Muhammadiyevich, Haydarov Musomiddin (American Journal of Bioscience and Clinical Integrity, 2025)
The purpose of the article: to describe the principles of rational antibacterial treatment of respiratory infections in real practice. Basic rules. The constant increase in the resistance of infectious disease pathogens and the sharp decrease in the number of new antibiotics make rational antibiotic therapy one of the urgent problems of modern medicine. Based on the analysis of current federal recommendations for the treatment of respiratory tract infectious diseases and the analysis of specific clinical examples, the article reviews the principles of antibacterial therapy for respiratory tract infections. Conclusion. The main principles of successful antimicrobial therapy are accurate diagnosis, selection of the initial antibiotic taking into account the causative agent involved in the development of the disease, the level of resistance in the country and region, as well as individual risk factors for infection with resistant pathogens; adherence to the exact dosage of the drug; correct assessment of the effectiveness and duration of antimicrobial therapy.